Analisis pengendalian kualitas pada mesin potong jahit dalam proses produksi Woven Bag menggunakan metode SQC dan FMEA di PT. XYZ - Wardani, Risma Dwi Sukma; Rahmawati, Nur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
XYZ is a company manufacturing plastic sacks, especially woven bags. During the production process, problems were discovered with the Sewing Cutting Machine (MPJ), which affected the quality of the final product. This research is aimed at identifying and analyzing problems and factors that cause damage to the machine. Therefore, the methods used are Statistical Quality Control (SQC) and Failure Mode and Effect Analysis (FMEA). Based on the results of research at (SQC), it was found that the most dominant defects were 34% loose stitching, 33.5% holes in sacks, 32.5% inappropriate sewing folds. Furthermore, based on the results of the FMEA analysis, it is known that the cause of the defect with the highest RPN value is a loose stitch of 240 with the cause being inconsistent thread tension. Recommendations for improvements that can be proposed are implementing an automatic control system to maintain the stability of thread tension and conducting operator training to ensure appropriate thread settings. The implementation of these improvements is expected to improve the overall quality of woven bag products.